Fibras alimentares na população de Pelotas-RS: hábito de consumo e fatores associados. - Madruga, Samanta Winck (2006)
OBJECTIVE: To verify the prevalence of inadequate dietary fiber consumption habit and evaluate its association with socioeconomic, demographic and behavioral characteristics. DESIGN: A cross-sectional population-based study. SETTINGS: Pelotas-RS. The city holds nearly 320.000 inhabitants and is located in Southern Brazilian. SUBJECTS: A representative sample of the population was selected by a two-stage strategy; 3993 subjects (≥ 10 years) were interviewed. RESULTS: Sample was mostly female, white skin color and nearly 70% belonged to C socioeconomic level or lower. Inadequate dietary fiber consumption habit was positive for 65.6% (CI95% 64.2 67.1) of the sample. A higher prevalence was observed among men and teenagers. Adjusted analysis for the overall sample showed an association between inadequate fiber consumption habit and male, adolescents, lower socioeconomic level, current smoker, sufficiently active and people having under four daily meals. The age group-stratified analysis showed different associated factors. For the adolescents group, living alone was a risk factor to inadequate dietary fiber consumption, for the adults group sex (male), current smoker, sufficiently active and under four daily meals and, among the elderly just sex (male) and current smoker. Lower socioeconomic level was associated to the outcome in all groups. CONCLUSIONS: Inadequate fiber consumption habit is highly prevalent in the population. We must highlight that, although inadequate intake is very common, teenagers are at a higher risk, suggesting public health actions focusing this particular age group. Public health initiatives to improve eating patterns, concerning fiber consumption habits, must consider the contrast derived from associated factors.